Clinical outcomes of endoscopic surveillance for gastric ulcers in populations with a high prevalence of gastric cancer - Lee, Young Bae; Han, Jaeho; Cho, Jeong Hyeon; Lee, Hong Sub (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Although surveillance endoscopy is recommended after the treatment of a benign gastric ulcer in Korea, improved survival, secondary to an endoscopic follow-up strategy, is controversial. Thus, the aim of this study was to understand the results of gastric ulcer surveillance endoscopy and to individualize surveillance endoscopy by analyzing known risk factors for gastric cancer. Materials and Methods: In total, 599 (M:F=424:175, median age=55.4 years) patients who were diagnosed with a gastric ulcer and who underwent follow-up endoscopy between January 2003 and August 2014 were retrospectively enrolled in this study. The final results and risk factors of follow-up endoscopy were analyzed. Results: Multivariate analysis of the data between the benign and malignant ulcer groups (benign: malignant= 575:24) showed that an elevated border and irregular margins, among other risk factors, were significant indicators of malignancy (p<0.05). Of the 599 patients, 15 (2.5%) were histologically malignant based on the first biopsy results. Nine (1.5%) patients had malignant ulcers on surveillance endoscopy, and all nine were found to have atypia or dysplasia on the first biopsy. Eight of the nine patients had malignant endoscopic features. Conclusion: Surveillance endoscopy for gastric ulcers may be unnecessary, except in cases of malignant and pre-malignant endoscopic features on the initial endoscopy.